The Point of View of the Student in Attrition Research - McKeown, Brent; Macdonell, Allan; Bowman, Charles (Canadian Journal of Higher Education, 1993)
Until the early 1970’s, research into attrition among postsecondary students was largely aimed at establishing correlations between the characteristics the students brought with them to an institution and dropping out. Virtually all of this research was unguided by any explicit theoretical framework. With the work of Spady (1970; 1971), and that of Tinto (1975), a model was provided which became the theoretical foundation for most subsequent research into the problem. The model was based fundamentally on part of Durkheim’s work on suicide, keying on the concept of integration. According to the model, those students who were integrated into the social and academic life of the institution were less likely to drop out, and the focus shifted to include not only "background" factors, but also the experiences of students after they were admitted to the institution. While creating the illusion of offering a clear theoretical framework, the key concepts of social and academic integration are only very loosely connected with the original Durkheimian idea. It is contended here that a firmer foundation for the development of an appropriate theoretical framework is more likely to arise out of a careful attempt to understand the actions of students in terms of the meanings things in their world have for them. Methodological techniques appropriate to this task are advocated, without denying the importance of many significant clues to be found in much of the current and past research in the field.